Empowering Township Elderly Women: Upcycling Post-Consumer Waste Clothes into Sustainable Livelihoods - Khumalo, Mduduzi; Patnaik, Sweta; Chisin, Alettia (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Post-consumer clothing waste poses significant environmental and economic challenges, with second-hand garments often discarded despite their potential for reuse. Addressing this issue requires solutions that reduce waste and empower communities, especially marginalised groups like elderly women in township settings. This study explores how upcycling post-consumer waste clothes, guided by cradle-to-cradle principles and co-design processes, can enhance sustainability and social empowerment among elderly women in a South African township. Adopting a qualitative, case-based approach, participants were engaged through Grandmothers Against Poverty and AIDS (GAPA). Second-hand clothes sourced from local stores served as raw materials. Data collection included semi-structured interviews, participant observations, and examination of final products. Initially, participants relied on intuitive sewing techniques. Later, an expert introduced a structured, step-by-step upcycling method, encouraging them to apply more deliberate design strategies. Participants exhibited resourcefulness and creativity before the expert's intervention without explicitly recognising their efforts as sustainable. After the expert-led workshops, their products showed improved quality, durability, and potential marketability. Participants recognised upcycling as personally enriching, potentially income-generating, and environmentally meaningful. They also expressed interest in sharing knowledge with other grandmothers, indicating a ripple effect of skill dissemination. This research demonstrates that blending community-based ingenuity with structured upcycling strategy guidance can transform second-hand clothing waste into a vehicle for environmental stewardship, social cohesion, and economic resilience. It illustrates how local craftsmanship, informed by sustainable design frameworks, can foster ecological sustainability and community empowerment